Patterns of Mucocutaneous Disorders in HIV-seropositive Patients and Relations with CD4 Counts at Sanglah General Hospital, Denpasar, Bali - Made Wardhana; Nila Wardani; Ivana Sugiarto; Made Puspawati; Elis Indira; Wiraguna, Swastika Adiguna (Journal of Global Pharma Technology, 2017)
Background: It is well known that more than 90% of HIV-infected patients will develop at least one type of dermatologic disorder during their HIV infection. As a result of the acquired immunodeficiency or the effect of the treatment, with an increased risk infectious skin condition which caused by viral, bacterial, and fungal infections, as well as inflammatory skin disease, have all been reported to increase as CD4+ T cells depleted.Objective: Our purpose was to evaluate the cutaneous manifestation in HIV/AIDS patients in dermatology-venerology polyclinic, Sanglah Hospital Denpasar. Subjects and Methods: Data was collected from medical records of HIV/AIDS patient whose came to the dermato-venerology department, Sanglah Hospital period 2007-2009.Results: During the three years period, noted 260 HIV/AIDS patients with cutaneous manifestation, 183 males, and 77 females. Those patients mostly in the age group 21-30 years old. Five most common cutaneous manifestation was condyloma acuminate for 59 patients (22,7%), dermatitis 27 patients (10,4%), drug eruptions 26 patients (10,0%), prurigo 24 patients (9,2%) and seborrheic dermatitis 23 patients (8,8%). Conclusion: Cutaneous manifestation in HIV/AIDS patients which dominated by males gender and age group 21-30 years old was very varied, in which the most common cutaneous manifestation is condyloma acuminate.Keywords: Cutaneous manifestations, HIV/AIDS.